Changing trends in technique of hysterectomy in abnormal uterine bleeding: a comparison between non descent vaginal hysterectomy versus laparoscopic assisted vaginal hysterectomy - Mani, Ankita; Agrawal, Anjana; Sharma, Kanchan; Kumar, Amit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hysterectomy is the commonest gynaecological surgery over the world. However, in India there is a huge lack in data regarding this surgery. The common indications are abnormal uterine bleeding (AUB), prolapse, pelvic inflammatory disease (PID) and pelvic pain. This study focuses on pros and cons of different routes of hysterectomy to decide a better approach of management. Aims and objective of the study were to compare non descent vaginal hysterectomy (NDVH) to laparoscopic assisted vaginal hysterectomy (LAVH) to determine better route of hysterectomy. Methods: A randomized prospective observational study conducted in Hind Institute of Medical Science, Barabanki over a period of 2 years on perimenopausal women undergoing hysterectomy for AUB for benign pathology. 100 patients were selected for the study and randomly divided in 2 groups NDVH and LAVH. Preoperative investigations, intra-operative and postoperative complications were compared. Results: The mean duration of surgery was found to be significantly less in NDVH group 71.24 minutes as compared to LAVH group 103.1 minutes. (p value <0.001). Number of patients requiring Blood transfusion during or after surgery was higher in LAVH group (21) than in NDVH (15) (p value <0.05) suggesting more blood loss in LAVH. Patients undergoing NDVH were having significant less postoperative pain visual analogue score 3.8 as compared to 5.4 in LAVH group (p value <0.001) .5 patients in LAVH group were having postoperative abdomen discomfort as compared to only 1 in NDVH group (p value <0.05). Conclusions: NDVH supersedes LAVH being faster, less expensive, less blood loss and cosmetically scarless surgery. However, LAVH should be kept in mind if there is associated adnexal pathology.